A Critical Review: Technology as Learning Media in Teaching Reading - Abdul Hakim; Wahyuni, Sri (J-SHMIC : Journal of English for Academic, 2024)
Reading is a language skill that makes it possible to understand information clearly, this skill is one of the basic skills that allows students to improve their performance. Technology is something interesting for students at this time, especially for the Generation Z students who were born around the year of 1995-2012. The purpose of this article is to do a Systematic Literature Review (SLR) on technology as learning media in teaching reading. This article will provide research on technology as a learning medial for teaching reading from 2015 to 2022 across several countries, primarily focusing on high school students. Various data collection methods were used, including questionnaires, interviews, tests, and observations. 14 studies examined the effectiveness of technology in teaching reading, highlighting its importance in creating engaging educational environments and improving reading skills through personalized learning experiences. These studies emphasized the transformative impact of technology-based tools, particularly apps, in enhancing reading skill development. Early reading media based on technology, incorporating visuals, animations, audio, and interactive quizzes, were found to enhance learning experiences, making reading more enjoyable and effective.